Whole genome sequencing of Phomopsis asparagi reveals molecular basis of asparagus stem blight pathogenesis - Duan, Lingtao; Li, Yunpeng; Lan, Bo; Yin, Changfa; Deng, Xing; Yang, Ziyu; Sun, Qinghua; Li, Baojia; Yang, Yingqing (Frontiers in Microbiology, 2025)
Asparagus (Asparagus officinalis L.), a nutritionally and medicinally valuable crop, faces significant yield and quality losses due to stem blight disease caused by the fungal pathogen Phomopsis asparagi (syn. Diaporthe asparagi). Despite the implementation of various control measures—including agronomic practices, resistant cultivars, chemical treatments, and biological controls—the lack of comprehensive understanding of the pathogen’s molecular pathogenesis has hindered the development of effective management strategies. In this study, we present the first whole-genome assembly of P. asparagi (50.94 Mb) through Illumina sequencing, which contains 4,362 predicted protein-coding genes. Functional annotation identified key virulence-associated pathways, particularly those related to oxidative stress response, reactive oxygen species (ROS) metabolism, cell wall remodeling, and programmed cell death (PCD). Given the known temperature sensitivity of disease development, we performed comparative transcriptomic profiling under optimal (25 °C) and heat-stress (32 °C) conditions. Our findings reveal that thermal stress triggers a sophisticated molecular response cascade in P. asparagi: initial environmental sensing through WRKY transcription factors and MAPK signaling activates coordinated stress adaptation mechanisms involving ROS generation, DNA damage repair, metabolic reprogramming (lipid and carbohydrate metabolism), proteolytic activity, and cell wall degradation enzymes. This multifaceted response ultimately culminates in host cell dysfunction and PCD, facilitating fungal invasion. This work provides fundamental genomic resources and mechanistic insights into P. asparagi pathogenicity, offering new targets for developing science-based disease control approaches in asparagus cultivation.